A driving power with filter compensator for micro-positioning improvement of piezoelectric bimorph actuators. Issue 1 (December 2020) - Chen, Wei; Chen, Yuansheng; Gu, Cong; Zhao, Pengcheng
Abstract: To improve the micro-positioning accuracy of piezoelectric bimorph actuators, a driving power was designed with filter compensator. Amplifier modular was designed with high-voltage operational amplifier, and filter compensator modular is responsible for charge signal. Simulation results show that the output of filter compensator modular is proportional to the electric charge on the actuator. Experimental results indicate that the maximum error is 10μm without filter compensator modular, and reduced to 5μm with proposed driving power.